PENINGKATAN KINERJA PEMASARAN MELALUI OPTIMALISASI KEUNGGULAN BERSAING - Irfanunnisa’ Tsalits Hartanty; Alifah Ratnawati (Jurnal Ekonomi dan Bisnis, 2013)
In the business world, competition is difficult to avoid. With the competition, the company will provide a better quality of the product or provide a cheaper price to attract more consumers. Through a competitive advantage, the company will be able to maintain continuity of production and develop the business to a larger scale. Therefore, this research tries to exam how to improve marketing performance through the optimization of competitive advantage . The predicted factors are: innovation, entrepreneurial orientation. Data about those variables was collected by conducting interviews with questionnaire to 46 respondents of SMEs. The data then were being analyzed using Interverning Regresion Method. The results of this research show thatall variables (innovation, entrepreneurial orientation.), have a positive impact on competitive advantage and marketing performance, while entrepreneurial orientation., has the biggest direct effect on the marketing performance. The result shows that while marketing performance as the dependent variable, ajusted R Square of 86.7%, while the remaining 13.3% explained by other variables not examined in this model. Then the competitive advantage as the dependent variable, ajusted R Square of 72.4%, while the remaining 27.6% explained by other variables not examined in this modelKeywords : competitive advantage, innovation, entrepreneurial orientation, marketingperformance.